Fundamentals of Entrepreneurship ENT 300 : Kueh Brother Bird Nest / Amelda Bachun ... [et al.] - Bachun, Amelda; Daniel, Benjamin Danrie; Awg Hamzani, Dayang Nurul Anina; Norariffin, Nur Azzah Azirah; Bolhasan, Nur'Shakila (2016)
The name of the company is Kueh Brother Bird Nest. The business is in form consultant which consists of five members. The main business activity is selling bird nest by their own (customer) transportation. We are selling the bird nest with the different price. It is because the price is depends on the kilogram (kg) of the bird nest that the customers wants and needs. Other than that, to get a high quality of the nest so that by our own customer can choose which bird’s nest that they want. This also can attract customer to be our regular customer. Our business operation is every day except public holiday at 0800 a.m. to 0500 p.m. There are no sleeping partners and all are entitled to participate in the consultant management. We agreed that Nur Azzah Azirah Binti Norariffin is our General Manager; Amelda Bachun is the Administration Manager, Dayang Nurul Anina Binti Awg Hamzani as the Marketing Manager, Benjamin Danrie Daniel as the Operational Manager and Nur’Shakila Binti Bolhasan as the Financial Manager. The selection of General Manager is based on consensus among all the partners and selected based on the experience, skills and ability. The General Manager is responsible in planning, leading, controlling and organizing the business. The Administration Manager is responsible for the job that related to administration such as planning and arranging the remuneration schedule of salary and wages. The Operation Manager is responsible to the entire job that related to the operation and will be supervise and coordinate the operation of the business. The Marketing Manager will be responsible to create the marketing plan, identifying the customer’s need and demand, identifying the competitors, target market, market size, and forecast the future market. Lastly, the Financial Manager will be handled the financial matters such as preparing the budget and financial statement for expenses of each departments and controlling the flow of the money of the organization.